A TSM control scheme of integrated guidance/autopilot design for UAV - Jinyong Yu; Qingjiu Xu; Yue Zhi (2011 3rd International Conference on Computer Research and Development, 2011)
A scheme for integrated guidance/autopilot design for some UAV based on terminal sliding-mode(TSM) control is proposed. Firstly, the terminal sliding mode control is introduced, then a guidance/control law is designed based on TSM control and the backstepping idea when an integrated guidance/autopilot model on the yaw plane of some UVA is formulated. Secondly, for the unavailable information of the maneuvering target, an estimating method is given and an auxiliary control based on a sliding mode estimator is used to offset the estimation error. Finally, a simulation of some UAV against high maneuvering targets on the yaw plane was made to verify the effectiveness and rightness of the scheme, and the simulation results have shown that good offensive performance can be got.